Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada PT HM Sampoerna Tbk Depok - Ridho Ardiansyah; Sunarti Sunarti (Journal of Management and Creative Business, 2026)
This study aims to determine and analyze the effect of work motivation and work discipline on employee performance at PT HM Sampoerna Tbk Depok. The background of this study is based on a decline in employee performance, which is evident from the decrease in work quantity and quality during the 2022–2024 period. The factors assumed to influence this condition are employee work motivation and work discipline. The research method used is a quantitative method with a descriptive associative approach. The population in this study consists of all 50 employees of PT HM Sampoerna Tbk Depok. The sampling technique uses saturated sampling, meaning the entire population is included as the research sample. Data collection was carried out through the distribution of questionnaires, interviews, and observations. Data analysis uses multiple linear regression assisted by the SPSS version 22.0 program. The results show that work motivation has a positive and significant effect on employee performance. Work discipline also has a positive and significant effect on employee performance. Simultaneously, work motivation and work discipline have a positive and significant effect on employee performance at PT HM Sampoerna Tbk Depok. Thus, improving work motivation and work discipline can enhance employee performance so that company goals can be achieved optimally.